Farmers' resilience behaviour in the face of water scarcity in the eastern part of Lake Urmia, Iran: an environmental psychological analysis - Shojaei‐Miandoragh, Mahdi; Bijani, Masoud; Abbasi, Enayat (Water and environment journal : WEJ, 2020)
This study aimed to perform an environmental‐psychological analysis of farmers' resilience behaviours towards water scarcity crisis. The study was descriptive‐correlational and causal‐relational and was carried out as a survey. The statistical population was composed of farmers in Aji‐Chay Basin in the eastern part of Lake Urmia (N = 417000), of whom 384 people were selected using stratified random sampling method. The instrument was a questionnaire whose validity was confirmed by a panel of experts. Its reliability was, also, verified using a Cronbach's alpha test and a pilot study (0.60 ≤ α ≤ 0.90). The findings presented the causal framework of farmers' resilience behaviour. The results of the causal analysis further indicated that the three variables of ‘place attachment’, ‘environmental attitudes’ and ‘environmental beliefs’ had the greatest impact on farmers' resilience behaviour towards water scarcity. The paper is concluded with some applied recommendations based on the findings.